Intelligent Queue Management System (i-Queue) for Patients in Hospital - Lee, Kai Li (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Queuing is a major challenge in the medical care industry. A proper queue management system can help to optimize the queue length, average waiting period, and the usage of the medical cares’ resources. Therefore, this project aims to design an Android mobile application which is to manage patients’ queues between patients and staffs in an effective way. The proposed system provides a portable platform to solve the current queueing system. Patients are able to join the queue virtually anywhere. At the same time, they able to monitor the queue status and a receive virtual ticket. Patients also able to notify when they are ready to be served.